OBSERVATION OF ENGLISH TEACHERS' TEACHING METHODS ON THE UNDERSTANDING OF STUDENTS IN CLASS 3A AT SD PELANGI ON THE SUBJECT OF DAILY ACTIVITIES - Eva Betty Simanjuntak; Dea Yuanita Nasution; Chelsi M Rajagukguk; Dwi Putri Sinaga; Rayani E M Sihombing; Sherin Fiona Sihombing (Jurnal Intelek Dan Cendikiawan Nusantara, 2025)
This study aims to examine how English teachers' teaching methods influence the understanding of 3A students at Pelangi Elementary School regarding the “Daily Activity” material. This study uses a qualitative approach with a case study method through observation, interviews, analysis of student documents, as well as photo and video documentation. The results show that teachers use a combination of lecture methods, question and answer sessions, visual media, and simple activities such as role-play. These methods make learning more interesting and easier to understand. The average score for student knowledge is 87.42 and their skills are 88.95, indicating that most students are able to understand simple vocabulary and sentences about daily activities. Factors that support successful learning include material that is relevant to students' lives, the use of clear media, attention to differences in student abilities, and a positive and motivating classroom atmosphere. This study concludes that a combination of lectures, question and answer sessions, and interactive activities can improve students' understanding of English learning in elementary school.